Isolation of Molds for Reducing the Color of Vinase - Kurniawan, Yahya; S. M., Hendro (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
Vinase or ethanol slop is blackish brown liquid, which is not friendly to the environment. Therefore, it is necessary the possibility to reduce the color biologically. The study was started by isolating molds from the vinase of Jatiroto Alcohol factory and the isolated molds was tested to study the capability of their color reduction. The results showed that there were 4 kinds of molds in the vinase i.e. : Rhizopus sp., Penicillium A, Penicillium B, and Aspergillus. Amongst these molds, Penicillium A and Penicillium B had the best potency in reducing the slop color. Around 54 % of its absorbency value at 420 nm could be reduced by the molds.